Pengaruh Penggunaan Jasa Influencer, Media Promosi Instagram Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Online (Studi Kasus Influencer Rachel Vennya Pada Produk Bittersweet By Najla) - Siti Nurfahria; Ayu Yulianti Putri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The purpose of this study was to determine and analyze the use of influencer services, Instagram promotion media and product quality which have a significant influence on online product purchasing decisions. This type of research is quantitative research with research methods in the form of data collection using a questionnaire. The data analysis model used is multiple linear regression analysis. The sample was selected by purposive sampling. The sample amounted to 100 respondents, using multiple linear regression analysis.The regression test results show that 72.30% of the factors of buying decisions can be explained by brands, price discounts and salespeople, while the remaining 27.70% is explained by other factors not examined in this study. While the results of the F test show that simultaneously the Influencer Service Usage, Instagram Promotion Media and Product Quality simultaneously have a positive and significant effect on buying decisions with the results of the analysis namely Fcount (87,016)> Ftable (2,700). The t test results show that the influencer service use variable shows the results of the tcount,¬ (0.060) and the Instagram Promotion Media variable shows the results of the analysis of tcount (3.727) while the product quality variable is 6.620 where the t table is (1.98498) then partially the Instagram promo media variable and product quality that has a positive and significant influence on online product purchasing decisions at Bittersweet by Najla The influencer service variable does not have a positive and significant effect on online product purchasing decisions at Bittersweet by Najla. The dominant variable affecting online product purchasing decisions at Bittersweet by Najla is Product Quality.